PERINTISAN KOMUNITAS SEL DI WILAYAH RANCAEKEK DAN SOREANG KABUPATEN BANDUNG - Christopher Alexander; Ferry Simanjuntak; Josef Christianto; Bait Adetya Situmorang; Michael Dendi Tinggogoy (Jurnal PKM Setiadharma, 2022)
Cell community planting is urgently needed, especially in areas where the gospel has not yet been reached. The data shows that the Rancaekek and Soreang areas are two areas the gospel has not reached. Therefore, the author makes pioneering efforts with the hope that one day there will be churches in Rancaekek and Soreang, starting with cell communities in these two areas. The method used in this research is study cases. The author conducts community worship services as the forerunner of the birth of a church of God. So far, the cell community services that have been held have received a positive response from the Christian families served. Those who still need a community to grow in faith in the area where they live show enthusiasm when their house is used as a place to carry out cell community worship. Cell community is carried out not only on-site but also online. This is an alternative response to the ongoing conditions (pandemic). If conditions improve in the future, an online cell community will likely be carried out on-site.